Event-related potentials reveal differential brain regions implicated in discounting in two tasks - Liam Delaney; Kevin John Denny; Wen Zhang; Caroline Rawdon; Richard A. P. Roche (University College Dublin, UCD School of Economics, 2008)
The way people make decisions about future benefits - termed discounting - has important implications for both financial planning and health behaviour. Several theories assume that, when delaying gratification, the lower weight given to future benefits (the discount rate) declines exponentially. However there is considerable evidence that it declines hyperbolically with the rate of discount being proportionate to the delay distance. There is relatively little evidence as to whether neural areas mediating time-dependent discounting processes differ according to the nature of the task. The present study investigates the potential neurological mechanisms underpinning domain-specific discounting processes. We present high-density event-related potentials (ERPs) data from a task in which participants were asked to make decisions about financial rewards or their health over short and long time-horizons. Participants (n=17) made a button-press response to their preference for an immediate or delayed gain (in the case of finance) or loss (in the case of health), with the discrepancy in the size of benefits/losses varying between alternatives. Waveform components elicited during the task were similar for both domains and included posterior N1, frontal P2 and posterior P3 components. We provide source dipole evidence that differential brain activation does occur across domains with results suggesting the possible involvement of the right cingulate gyrus and left claustrum for the health domain and the left medial and right superior frontal gyri for the finance domain. However, little evidence for differential activation across time horizons is found.
hdl:10197/594
Keywords: 330; Decision Making; Domain-Specific Discounting; Event-Related Potentials